Os sentido subjetivos de um jovem com história de transgressão social-legal na contemporaneidade - Gramkow, Gabriela (2007)
This study, based on a Social-Historical Psychology perspective, characterizes a young man identified in juridical and social terms as a practitioner and victim of violence. It proposes its objective as an approach of a socio-legal transgression phenomenon, focusing the subjective senses of this young man with criminal activity at the same time, using dialectical logic as a method of understanding reality. It is based on an objective and subjective research of the active and living process with the purpose of producing something new, trying to overcome knowledge committed to a critical and alternative psychology (Ozella, 2003b), as well as contributing to its analysis. Focusing on subjectivity, it approaches from a qualitative angle the constituent processes, taking into consideration the plasticity of the subjective phenomenon. It aims at a non-pathological view of human development, perceiving it as historical. The research took place in the historical and situational context of the city of Brasilia and looks towards a discussion of the forms of subjectivity in social life created by the differentiated story of this adolescent in conflict with the law, shaping the research as a case study . The interview, guided by the concept of conversation (González Rey, 2005a) is the principal instrument of data collection. In order to understand the subjective senses of this young man with a history of social and legal transgression, the study uses the approach of Qualitative Epistemology (González Rey, 2002). The interpretative processes produced three clusters of meanings: the social transgression impregnated in his life story; the strategies of subjective reconstruction and the process of assimilating what was learned. It analyzes social transgression as a fighting process emerging from the strange subject situated in human dregs as an activity interfacing with the production of meanings in the young man s life, and constituting the subjective configuration. Transgression marks the life story of this young man, connected by cultural constructions with deep transformations, subjective and objective, in his understanding of himself